Trends in Factors Affecting Pregnancy Outcomes Among Women With Type 1 or Type 2 Diabetes of Childbearing Age (2004–2017) - Gaudio, Mariangela; Dozio, Nicoletta; Feher, Michael; Scavini, Marina; Caretto, Amelia; Joy, Mark; Van Vlymer, Jeremy; Hinton, William; de Lusignan, Simon (Frontiers in Endocrinology, 2021)
Aim To describe trends in modifiable and non-modifiable unfavorable factors affecting pregnancy outcomes, over time (years 2004–2017), in women with diabetes of childbearing age from an English primary care perspective. Methods We identified women with diabetes aged 16–45 years from the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) network, an English primary care sentinel database. Repeated annual cross-sectional analyses (2004–2017) assessed the prevalence of unfavorable factors for pregnancy, such as obesity, poor glycaemic control, microalbuminuria, hypertension, use of medications for treating diabetes, and associated comorbidities not recommended for pregnancy. Results We identified 3,218 women (61.5% with Type 2 diabetes) in 2004 and 6,657 (65.0% with Type 2 diabetes) in 2017. The proportion of women with ideal glycaemic control for conception (HbA1c<6.5%) increased over time, in patients with Type 1 diabetes from 9.0% (7.1%–11.0%) to 19.1% (17.2%–21.1%), and in those with Type 2 diabetes from 27.2% (24.6%–29.9%) to 35.4% (33.6%–37.1%). The proportion of women with Type 2 diabetes prescribed medications different from insulin and metformin rose from 22.3% (20.5%–24.2%) to 27.3% (26.0%–28.6%). In 2017, 14.0% (12.6%–15.4%) of women with Type 1 and 30.7% (29.3%–32.0%) with Type 2 diabetes were prescribed angiotensin-modulating antihypertensives or statins. We captured at least one unfavorable factor for pregnancy in 50.9% (48.8%–52.9%) of women with Type 1 diabetes and 70.7% (69.3%–72.0%) of women with Type 2 diabetes. Only one third of women with Type 1 diabetes (32.2%, 30.3%–34.0%) and a quarter of those with Type 2 diabetes (23.1%, 21.9%–24.4%) were prescribed hormonal contraception. Contraception was prescribed more frequently to women with unfavorable factors for pregnancy compared to those without, however, the difference was significant only for women with Type 1 diabetes. Conclusions Despite significant improvements in general diabetes care, the majority of women with Type 1 or Type 2 diabetes have unfavorable, although mostly modifiable, factors for the start of pregnancy. Good diabetes care for women of childbearing age should include taking into consideration a possible pregnancy.